Controlled growth of citrate-stabilized gold nanoparticles using a semi-continuous seed-mediated route - Muhammad Bilal; Sulalit Bandyopadhyay (Discover Nano)
Abstract Gold nanoparticles (Au NPs) hold unique optical and electronic properties due to their surface plasmon resonance. The size, shape, and surface chemistry of Au NPs are key parameters for altering their optical properties to fine-tune Au NPs for specific applications. We report a size-controlled synthesis of citrate-stabilized Au NPs via the Turkevich method, followed by their growth through a semi-continuous seed-mediated approach. Au NPs of up to 53 nm were synthesized by controlled addition of chloroauric acid (HAuCl₄) to pre-prepared citrate stabilized Au NP seeds. Our approach leverages the residual sodium citrate from the Turkevich reaction to reduce HAuCl₄ during seed-mediated growth of Au NPs. Notably, we observed that a boiling temperature, as opposed to 70 °C, provided better control over nanoparticle size and morphology. Our method addresses several challenges associated with seed-mediated growth by yielding relatively spherical, monodisperse, citrate-stabilized, water-dispersible Au NPs in a single growth step, without sacrificing yield. Furthermore, a kinetics study revealed a continuous increase in particle diameter over the reaction period, hinting at the continuous and uniform growth of Au NPs.